Purchasing Power Parity (France and US) - Almutairi, Ebtihal N; Almutairi, Hind N (Advances in Social Sciences Research Journal, 2021)
Purchasing power parity is an important economic concept that presents a useful way of analyzing various currencies by comparing a similar basket of goods. Essentially, the concept of purchasing power parity (PPP) implies that the purchasing power parity will be same for two countries if their currencies fetch the same basket of goods, thereby allowing a measure to assess and compare different currencies. In order to test this concept and presence of purchasing power parity between countries, this essay aims to extend a statistical exercise for assessing the PPP for France and USA for both the long and short run. The data used is a monthly time series for the price indexes for France, US, and the nominal and real exchange rates. Keywords: Purchasing power parity; economic; Augmented Dickey Fuller; Fuller test; Vector autoregressive model